Ethnobotany of Medicinal Plants of the Sumba Trible in Central Sumba Regency, East Nusa Tenggara Timur - Ariski Vevi Liswandari; Sulisetijono; Frida Kunti Setiowati (Universitas Brawijaya, 2023)
The Sumba tribe is a local community that inhabits Sumba Island, one of which is in Central Sumba Regency. The majority of the people of the Sumba Tribe still have close interactions with nature, one of which is still using plants used for traditional medicine. This traditional medicine has been carried out for a long time and has become a tradition passed down from generation to generation in the customs of the Sumba people. This study aims to determine the diversity of plant species used for medicine by the Sumba people, the Use Value Index per species (UVs), and the Index of Cultural Significance (ICS) of medicinal plants in Central Sumba Regency. This study used the snowball sampling method by conducting open-ended interviews. The results of this study have found a diversity of plants that have potential as medicine. It is known that there are 116 species of medicinal plants used by the people of the Sumba tribe for medication. Medicinal plants can be found in the yard of the house. Based on the analysis of UVs, it was found that the species with the highest use value (Andrographis paniculata Ness), had the highest UVs (5.60), while for the ICS analysis, papaya (Carica papaya L.) had the highest ICS value (850).